2000
DOI: 10.1080/03079450020016832
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Salmonella enteritidis phage types 4, 8 and 23 in specific pathogen free chicks

Abstract: The pathogenicity of two isolates of Salmonella enterica serovar Enteritidis (SE) phage type (PT) 4, three of PT8 and one of PT23 was investigated in groups of 1-day-old specific pathogen free White Leghorn chicks. Two groups were crop gavaged with each culture but at two different doses. Two additional groups were given Salmonella enterica serovar Pullorum (SP) at similar doses and one further group served as uninoculated controls. Body weights were recorded at 14, 21, and 28 days postinoculation (d.p.i), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
6
10
1
1
Order By: Relevance
“…It has been published previously by others that the Salmonella Enteritidis PT4 infection of chicks causes full white ceca due to infiltration by white blood cells (1,2,16,36,42). We found these cecal abnormalities in our studies.…”
Section: Vol 77 2011supporting
confidence: 80%
See 2 more Smart Citations
“…It has been published previously by others that the Salmonella Enteritidis PT4 infection of chicks causes full white ceca due to infiltration by white blood cells (1,2,16,36,42). We found these cecal abnormalities in our studies.…”
Section: Vol 77 2011supporting
confidence: 80%
“…3). In addition, only birds treated with predatory wild-type Bdellovibrio had a significantly smaller proportion of abnormal ceca (which showed inflammatory characteristics described previously [1,2,16,36,42]) than that of untreated controls (Table 1 and Fig. 4).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Between the evaluated lesions, aerossaculitis, peritonitis and onfalitis were the most common occurrences in both studied serotypes. These findings are similar to the ones described by many researches after experimental infection with S. Enteritidis (Desmidt et al, 1997;Dhillon et al, 1999;Alisantosa et al, 2000;Dhillon et al, 2001;Akthar et al, 2011;Akthar et al, 2013) and S. Typhimurium in Specific Pathogens Free (SPF) birds between one and twenty-eight days.…”
Section: Resultssupporting
confidence: 91%
“…Based on this, it is suggested that both serotypes have the potential to cause septicemic lesions such as the ones caused by the avian specific serotypes. This hypothesis is suggested by other authors who have found the same macroscopic alterations after experimental inoculation with S. Enteritidis, S. Typhimurium, and S. Pullorum (Alisantosa et al, 2000;Dhillon et al, 2001;Roy et al, 2001). (Smith and Tucker, 1980).…”
Section: Resultssupporting
confidence: 69%